Penanaman nilai-nilai karakter dalam pembelajaran tematik kelas rendah di Kota Madya Yogyakarta - Nugroho, Irfan Adi; Nartani, C. Indah; Nofrida, Eka Ridha; Amalia, Sholihati (CV. Kurnia Grup, 2024)
This study aims to: 1) describe character values in character values developed in thematic learning of low-grade elementary schools in Kota Madya Yogyakarta; 2) describe the strategy of presenting character values in low-grade thematic learning in Kota Madya Yogyakarta. The expected output of this study is a research report related to character values in thematic learning in low-grade elementary schools and publications in scientific journals. The research method used is a qualitative descriptive method with the researcher as the key instrument. Data collection is carried out by the note-taking method. Data analysis is qualitative descriptive. The object of research is the cultivation of character values in the Madya City of Yogyakarta. Data analysis includes data reduction, data presentation, data verification, and triangulation.